Marketing Responses to the Taxation of Soft Drinks; Comment on “Understanding Marketing Responses to a Tax on Sugary Drinks: A Qualitative Interview Study in the United Kingdom, 2019” - Leigh Sparks (International Journal of Health Policy and Management, 2023)
The paper by Forde et al provides a useful qualitative consideration of marketing responses to the implementation of the 2018 Soft Drinks Industry Levy (SDIL) in the United Kingdom. This commentary discusses that paper and its conclusions and seeks to place them in a broader context for marketing, fiscal measures and health and public policy. It suggests that modern conceptualisations of marketing and wider considerations of market and non-market strategies could provide a valuable lens to understand the ways in which companies and sectors respond to the threats they perceive and the constantly changing sectoral opportunities. It is important that fiscal measures introduced have the desired effects, and that not only positive behaviours (whether of companies or consumers) are incentivised, but that adverse behaviours are actively disincentivised.